Application of polyetheretherketone temporal muscle prostheses for temporal hollowing following cranioplasty - Yang, Xiaoyu; Zhang, Yi; Guan, Junwen (Frontiers in Neurology, 2025)
BackgroundDecompressive craniectomy is an effective intervention for refractory intracranial hypertension. However, subsequent cranioplasty, though technically less demanding, is associated with a non-negligible incidence of complications. Among these, temporal hollowing is a common yet frequently overlooked sequela that significantly compromises facial aesthetics and can lead to various psychosocial issues.MethodsBased on the pathophysiological mechanisms underlying temporal hollowing following cranioplasty and incorporating clinical experience from West China Hospital, Sichuan University, this study explores the application of 3D-printed polyetheretherketone (PEEK) temporal muscle prostheses for correcting temporal hollowing after 3D-printed PEEK cranioplasty. The approach involves precise measurement of the contralateral temporal muscle dimensions and volumetric assessment of the atrophied ipsilateral muscle to fabricate patient-specific 3D-printed PEEK implants. These customized prostheses are then surgically implanted in a secondary procedure to restore temporal contour symmetry.ConclusionTemporal hollowing represents a frequent sequela of cranioplasty, arising from multifactorial mechanisms and often contributing to psychosocial challenges. The patient-specific 3D-printed PEEK temporal muscle prosthesis, developed based on contralateral temporal muscle metrics at West China Hospital, offers a precise and individualized solution for restoring temporal contour symmetry.